Effects of probiotic melon juice on blood pressure in patients with pre-hypertension - Nadilla Putri Sp; Tonny Cortis Maigoda; Desri Suryani; Jumiyati Jumiyati (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Potassium intake can lower systolic and diastolic blood pressure, whereas low sodium consumption can increase blood pressure. Although the use of fruits and probiotics as alternative drinks to reduce blood pressure has been widely practiced, research on the combination of fruit juice and probiotics from melon juice is still very rare. This study aimed to measure the effect of administering fruit juice with a combination of probiotics and melon juice on blood pressure in prehypertensive patients. An experimental research design with a randomized group design was conducted at the Jembatan Kecil Health Center, Bengkulu City, in 2024. A total of 28 respondents were selected using purposive sampling, The instruments used were digital blood pressure and 24-hour recall form, with statistical analysis using ANOVA and Duncan’s test. Results, showed that the average systolic and diastolic blood pressure before the intervention was 138/87 mmHg, and after the intervention dropped to 122/79 mmHg. There were differences in systolic (p=0,000) and diastolic (p=0,006) blood pressure between the treatment groups, with the third treatment showing the greatest effect. In conclusion, fruit juice with a combination of probiotic melon juice has a significant effect in reducing blood pressure in prehypertensive patients and has a harmless effect, which can be used as a non-medical treatment for prehypertensive patients.